Investigation of Bronsted acidity in zeolites through adsorbates with diverse proton affinities - Trachta, Michal; Bludsky, Ota; Vaculík, Jan; Bulánek, Roman; Rubeš, Miroslav (Nature Publishing Group, 2023)
Understanding the adsorption behavior of base probes in aluminosilicates and its relationship to the intrinsic acidity of Bronsted acid sites (BAS) is essential for the catalytic applications of these materials. In this study, we investigated the adsorption properties of base probe molecules with varying proton affinities (acetonitrile, acetone, formamide, and ammonia) within six different aluminosilicate frameworks (FAU, CHA, IFR, MOR, FER, and TON). An important objective was to propose a robust criterion for evaluating the intrinsic BAS acidity (i.e., state of BAS deprotonation). Based on the bond order conservation principle, the changes in the covalent bond between the aluminum and oxygen carrying the proton provide a good description of the BAS deprotonation state. The ammonia and formamide adsorption cause BAS deprotonation and cannot be used to assess intrinsic BAS acidity. The transition from ion-pair formation, specifically conjugated acid/base interaction, in formamide to strong hydrogen bonding in acetone occurs within a narrow range of base proton affinities (812-822 kJ mol(-1)). The adsorption of acetonitrile results in the formation of hydrogen-bonded complexes, which exhibit a deprotonation state that follows a similar trend to the deprotonation induced by acetone. This allows for a semi-quantitative comparison of the acidity strengths of BAS within and between the different aluminosilicate frameworks.
Studium Bronstedovy kyselosti v zeolitech prostřednictvím adsorbátů s různou protonovou afinitou ​
Keywords: initio molecular-dynamics; nmr chemical-shifts; solid acids; scaling relations; reactivity; catalysts; strength; transition; adsorption; simulation; molekulární dynamika; NMR; kyselost; katalyzátor; zeolit; adsorpce; simulace